Kinetic behaviour of free lipase and mica-based immobilized lipase catalyzing the synthesis of sugar esters - Zaidan, Uswatun Hasanah; Abdul Rahman, Mohd Basyaruddin; Othman, Siti Salhah; Basri, Mahiran; Abd. Malek, Emilia; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (Japan Society for Bioscience, Biotechnology, and Agrochemistry, 2011)
The utilization of natural mica as a biocatalyst support in kinetic investigations is first described in this study. The formation of lactose caprate from lactose sugar and capric acid, using free lipase (free-CRL) and lipase immobilized on nanoporous mica (NER-CRL) as a biocatalyst, was evaluated through a kinetic study. The apparent kinetic parameters, K(m) and V(max), were determined by means of the Michaelis-Menten kinetic model. The Ping-Pong Bi-Bi mechanism with single substrate inhibition was adopted as it best explains the experimental findings. The kinetic results show lower K(m) values with NER-CRL than with free-CRL, indicating the higher affinity of NER-CRL towards both substrates at the maximum reaction velocity (V(max,app)>V(max)). The kinetic parameters deduced from this model were used to simulate reaction rate data which were in close agreement with the experimental values.